Population dynamics of island populations of subarctic Clethrionomys rutilus - Burns, Gordon R. (Canadian Journal of Zoology, 1981)
Populations of Clethrionomys rutilus were studied on two islands (Island 2 and Green Island) in the Mackenzie River during the summers of 1976 to 1978. This was done to examine the demographic parameters related to confinement of northern red-backed vole populations on islands.The number of voles on Island 2 in 1977 increased until late June and then remained nearly constant until trapping ceased in late August. On Green Island in 1977 and 1978 and Island 2 in 1978, populations grew all summer and even in August had not reached the densities found during the 1977 high on Island 2. Island 2 in 1977 had an unusually low number of maturing young voles. Higher wounding rates and shorter adjusted range lengths were associated with higher population densities.Although high densities of voles were reached early in the summer of 1977 on Island 2, numbers stopped increasing before the end of the breeding season. Restraint of growth potential was seen in poor maturation of the young and in declining juvenile survival and recruitment of young through summer.